2016
DOI: 10.2147/eb.s82670
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury and vestibulo-ocular function: current challenges and future prospects

Abstract: Normal function of the vestibulo-ocular reflex (VOR) coordinates eye movement with head movement, in order to provide clear vision during motion and maintain balance. VOR is generated within the semicircular canals of the inner ear to elicit compensatory eye movements, which maintain stability of images on the fovea during brief, rapid head motion, otherwise known as gaze stability. Normal VOR function is necessary in carrying out activities of daily living (eg, walking and riding in a car) and is of particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…The authors mentioned that the widely distributed central and peripheral components of the vestibular system makes it vulnerable to the translated forces experienced during TBIs. Despite extensive studies being published on the prevalence of vestibular dysfunction due to TBI in adults (66)(67)(68), there is a substantial gap in literature concerning the pediatric population. We, in this present review, included only three studies evaluating the prevalence of vestibular dysfunction due to TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The authors mentioned that the widely distributed central and peripheral components of the vestibular system makes it vulnerable to the translated forces experienced during TBIs. Despite extensive studies being published on the prevalence of vestibular dysfunction due to TBI in adults (66)(67)(68), there is a substantial gap in literature concerning the pediatric population. We, in this present review, included only three studies evaluating the prevalence of vestibular dysfunction due to TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the rapid eye function include increased latency to eye movement (165 ms concussion vs. 149 ms control) when a stimulus is presented and an increased error distance (1.11 cm concussion vs. 0.86 cm control) during rapid eye movement tasks. 60,61 Cranial nerve issues may be present due to asymmetrical eye movements during rapid eye movements. 60 Further rapid eye movement abnormalities are noted when slow object tracking is performed in the manner of frequent update rapid eye movements onto the object of focus.…”
Section: Eye Movementsmentioning
confidence: 99%
“…60,61 Cranial nerve issues may be present due to asymmetrical eye movements during rapid eye movements. 60 Further rapid eye movement abnormalities are noted when slow object tracking is performed in the manner of frequent update rapid eye movements onto the object of focus. 60 Previous literature has reported that patients suffering from a concussion have an increased amount of errors and deficits in the prediction of targets during object tracking.…”
Section: Eye Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of mild head injury, the symptoms of the post-concussion syndrome, including those of the balance system, may last for a year or even longer in 10 -15% of patients, and this percentage increases to 28% in moderate traumatic injuries [1,21]. Dizziness after brain injury is also a risk factor for a prolonged recovery [22].…”
Section: Introductionmentioning
confidence: 99%